Leadership Support and Organizational Performance: The Mediating Role of Employee Satisfaction - Dilli Ram Bhandari, (Pravaha, 2022)
This study has been carried out to explore the effect of Leadership Support on Organizational Performance with the mediating effect of Employee Satisfaction in Nepalese Commercial Banks. A survey has been undertaken to gather the data by use of a structured questionnaire from 6 banks. Altogether, 224 questionnaires were used for final analysis. Both exploratory and confirmatory factor analyses were taken for data analysis. The collected data were analyzed on two steps. Exploratory Factor Analysis and Confirmatory Factor Analysis. The result of the data analysis revealed that Leadership Support significantly affects Organizational Performance and Employee Satisfaction. Further, Employee Satisfaction showed the direct positive impact on Organizational Performance and it also showed a mediating effect between Leadership Support and Organizational Performance. The findings of this study imply that human factor should be emphasized for a better Organizational Performance and Leadership Support plays a vital role in satisfying and motivating the employees.